A high nuclear basal level of ERK2 phosphorylation contributes to the resistance of cisplatin-resistant human ovarian cancer cells - Lee, Sooyong; Yoon, Seunghee; Kim, Dong-Hyun (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2007)
Objective. The aim of this study was to elucidate the role of ERK 1/2 on cisplatin resistance in human ovarian cancer cells. Methods. The relationship between nuclear levels of ERK2 and cisplatin-induced apoptosis in human ovarian carcinoma cell line, OVCAR-3, and in cells of the cisplatin-resistant subclone, OVCAR-3/CDDP, was examined using immunoblotting and immunocytochemistry. Results. Cisplatin treatment resulted in the activation of ERK2, both in OVCAR-3 and OVCAR-3/CDDP cells. However, considerable levels of activated ERK2 existed in the nuclei of OVCAR-3/CDDP cells during serum starvation and in the early period (1-3 h) after cisplatin treatment. Conversely, phospho-ERK2 was marginally detected in the nuclei of OVCAR-3 cells prior to cisplatin treatment. These phenomena were confirmed by immunofluorescence staining of the phosphorylated ERK2 in the nuclei of both cells. High basal phospho-ERK2 in the nuclei of OVCAR-3/CDDP cells contributed to cisplatin resistance, and was supported by several observations; (1) treatment of U0126, an inhibitor of MEK/ERK signaling pathway, partially sensitized OVCAR-3/CDDP cells to cisplatin; (2) pretreatment of OVCAR-3 cells with phorbol 12-myristate 13-acetate (PMA), an activator of ERK, induced nuclear translocation of activated ERK2, which led to the suppression of cisplatin-induced apoptosis. Conclusions. These results collectively indicate that prelocalization of activated ERK2 in the nuclei contribute to cisplatin resistance in OVCAR-3/CDDP cells. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: SIGNAL-REGULATED KINASE; ACTIVATED PROTEIN-KINASE; MAP KINASE; INDUCED APOPTOSIS; CARCINOMA CELLS; LEUKEMIA-CELLS; JURKAT CELLS; INHIBITION; PATHWAY; CASCADE